Utilizing Virtual Reality in Architectural Presentation : System Model - Mohd. Jaaffar, Salleh (2003)
This project is carried out to develop a system model of virtual reality (VR) architectural presentation model. Three objectives have been underlined; to hands on the development process and tools, to complete a VR architectural presentation system model and to identify the advantanges of VR architectural presentation. Several steps have been taken starting with information gathering and analyzing, developing a 3D model, format conversion, creating a VR environment, system testing and system implementation. AutoCAD, 3D Studio, Adobe Photoshope and UnrealtyEd are the involved software in this project. Along the process the author has gained real experience especially in integrating the 3D model to VR package and utilizing VR development tool. The finished virtual building model is experienced by navigating around and inside the model. In conclusion VR technique has better visualization approach compared to the other techniques which are commonly used by architect firms. Further research can be made by using this system model or the knowledge gained while developing it as basis for research about the architect firms acceptance.